Nanomaterials as a new frontier platform: metal-doped and hybrid carbon dots as enzyme mimics for environmental applications - Yousaf, Aiman; Imran, Muhammad; Farooq Warsi, Muhammad; Alsafari, Ibrahim A.; Khan, Farhan A.; Parra-Saldívar, Roberto; Gutiérrez-Soto, Guadalupe; Iqbal, Hafiz M. N. (Frontiers in Materials, 2025)
Environmental pollution has become an inexorable problem for the planet Earth. The precise detection and degradation of heavy metals, pesticides, industrial-, pharmaceutical- and personal care- products is needed. Nanotechnology holds great promise in addressing global issues. Over the past decades, nanozymic nanomaterials have exceptionally overcome the intrinsic limitations of natural enzymes. Carbon dots (CDs) exhibit unique structures, surface properties, high catalytic activities, and low toxicity. Different techniques, such as doping or surface passivation, can enhance these exceptional properties. Doping modifies CDs’ electronic, magnetic, optical, and catalytic properties considerably. Metal doping, a more significant strategy, involves the introduction of metallic impurities, which offer insight into enhancing the physicochemical properties of CDs. Metal-doped CDs exhibit higher optical absorbance and catalytic performance than pristine CDs. The literature shows that researchers have utilized various synthetic approaches to fabricate CDs-Metal nanozymes. Researchers have reported the metal-doped and hybrid CDs’ peroxidase, catalase, laccase, and superoxide dismutase-like activities. These metal-doped nanozymes put forward substantial environmental remediations and applications such as sensing, photocatalytic degradation, adsorption, and removal of environmental contaminants. This review thoroughly discussed the metal-based functionalization of CDs, the enzyme-like properties, and the ecological applications of metal-doped and hybrid enzymes. The review also presents the current novelties, remaining challenges, and future directions with key examples.